PENGARUH NILAI HLB KOMBINASI EMULSIFIER PADA FORMULASI BODY LOTION MENGANDUNG EKSTRAK DAUN PUCUK MERAH (Syzygium myrtifolium Walp.) - Bannan Muthi'atul Af'idah (Akademi Farmasi Yamasi Makassar, 2026)
The utilization of natural ingredients in cosmetic formulations is continuously increasing due to their perceived higher safety profile. Red lip (Syzygium myrtifolium Walp.) leaves possess potent antioxidant activity, rendering them highly potential for utilization as an active ingredient in cosmetic preparations to promote skin health. This study aimed to formulate a body lotion containing red lip leaf extract and to evaluate the effect of the Hydrophilic-Lipophilic Balance (HLB) values of combined emulsifiers, specifically Tween 80 (HLB = 15) and Span 80 (HLB = 4.3), on the physical quality and stability of the resulting body lotion. The formulations were developed by varying four levels of the combined emulsifier HLB values, ranging from HLB 9 to 12. The evaluated physical quality parameters encompassed organoleptic properties, homogeneity, spreadability, acidity (pH), viscosity, and physical stability utilizing the cycling test method. Statistical analysis demonstrated that variations in the HLB values exerted a significant effect on the spreadability, pH, and viscosity of the formulations. Formula 2 (HLB 10) exhibited the physical characteristics that complied with the SNI 16-4399-1996 standard and demonstrated the best physical stability. This study indicates that the HLB value of the Tween 80 and Span 80 emulsifier combination plays a critical role in maintaining the structural integrity and preserving the physical quality of the lotion formulations.